Developmental trajectory of narrative skills in typically developing Cypriot-Greek-speaking children: Implications for language assessment - Papastefanou, Theodora; Theodorou, Elena (My University, 2025)
Oral narratives are important for assessing children as narratives provide useful information about children's language development. This study aimed to explore how the narrative skills of Cypriot-Greek speaking children develop in the domains of syntactic productivity, complexity, and lexical diversity, during their preschool and primary school years. Additionally, the study sought to determine whether there was any difference in the performance of boys and girls on the narrative measures. One hundred and twenty-nine 4–9-year-old typically developing Cypriot-Greek-speaking children were recruited for the study. The Renfrew Bus Story was administered to elicit narratives, and microstructure measures were calculated and analysed. The results showed that there were developmental changes in three measures of syntactic productivity (number of C-units and total number of words) and lexical diversity (number of different words). On the contrary, measures of syntactic complexity (MLU-word, number of subordinate clauses and mean of the five longest sentences) did not significantly differentiate children between the three groups. In addition, the results showed no significant gender effect on narrative skills. This study provides initial evidence in retelling narrative development patterns on typically developing Cypriot-Greek-speaking children. Speech and language therapists can use this knowledge to compare children’s performance and detect children who are at high risk of experiencing language disorders.
Keywords: Retelling; typical language development; Cypriot-Greek bilectal childrent